Association between ambient air pollution and hyperuricemia in traffic police officers in China: a cohort study. Issue 1 (2nd January 2021) - Tang, Yong-Xiang; Bloom, Michael S.; Qian, Zhengmin (Min); Liu, Echu; Jansson, Daire R.; Vaughn, Michael G.; Lin, Hua-Liang; Xiao, Lv-Wu; Duan, Chuan-Wei; Yang, Lie; Xu, Xiao-Yun; Li, Yan-Ru; et al.
ABSTRACT: To evaluate the association between ambient air pollution and hyperuricemia, we prospectively followed 1748 traffic police officers without hyperuricemia at baseline (2009–2014) from 11 districts in Guangzhou, China. We calculated six-year average PM10, SO2 and NO2 concentrations using data collected from air monitoring stations. The hazard ratios for hyperuricemia per 10 µg/m 3 increase in air pollutants were 1.46 (95% CI: 1.28–1.68) for PM10, 1.23 (95% CI: 1.00–1.51) for SO2, and 1.43 (95% CI: 1.26–1.61) for NO2 . We also identified changes in the ratio of serum uric acid to serum creatinine concentrations (ua/cre) per 10 µg/m 3 increase in air pollutants as 11.54% (95% CI: 8.14%-14.93%) higher for PM10, 5.09% (95% CI: 2.76%-7.42%) higher for SO2, and 5.13% (95% CI: 2.35%-7.92%) higher for NO2, respectively. Long-term exposure to ambient air pollution was associated with a higher incidence of hyperuricemia and an increase in ua/cre among traffic police officers.